Highly Efficient Biphoton Generation from Thin Dense Atomic Ensemble - Heewoo Kim; Hansol Jeong; Han Seb Moon (Advanced Photonics Research)
Hybrid photonic quantum networks require photonic quantum states generated from different systems, such as atoms and quantum dots. Photonic quantum sources based on atomic ensembles are excellent candidates due to their brightness, low noise, and narrowband characteristics. Herein, a new platform for a highly efficient biphoton source is presented using a thin, dense atomic medium from a hot 1 mm‐long chip‐scale Cs atomic vapor cell. Strongly correlated bright biphotons are generated via spontaneous four‐wave mixing from a dense atomic ensemble based on the 6S1/2–6P3/2–6D5/2 transition of 133Cs. Biphoton source achieves a detected biphoton count rate of 100 kilo‐counts per second, a heralding efficiency of 15%, and a maximum normalized crosscorrelation function value of 100 between the signal and idler photons, despite the low detector efficiency of a silicon avalanche photodetector being less than 25% at 917 nm. Herein, the maximal violation of the Cauchy–Schwarz inequality by a factor greater than 106 at a pump power of 1 μW is obtained. The scheme for a highly efficient photon source is believed to be useful for scalable quantum networks.